Functionalization Strategies of PEDOT and PEDOT:PSS Films for Organic Bioelectronics Applications - Fenoy, Gonzalo Eduardo (2021)
Organic bioelectronics involves the connection of organic semiconductors with living organisms, organs, tissues, cells, membranes, proteins, and even small molecules. In recent years, this field has received great interest due to the development of all kinds of devices architectures, enabling the detection of several relevant biomarkers, the stimulation and sensing of cells and tissues, and the recording of electrophysiological signals, among others. In this review, we discuss recent func-tionalization approaches for PEDOT and PEDOT:PSS films with the aim of integrating biomolecules for the fabrication of bioelectronics platforms. As the choice of the strategy is determined by the conducting polymer synthesis method, initially PEDOT and PEDOT:PSS films preparation methods are presented. Later, a wide variety of PEDOT functionalization approaches are discussed, together with bioconjugation techniques to develop efficient organic-biological interfaces. Finally, and by making use of these approaches, the fabrication of different platforms towards organic bioelectronics devices is reviewed.